Predicting collision‐induced dissociation mass spectra: understanding the role of the mobile proton in small molecule fragmentation. (15th May 2016) - Wright, Patricia; Alex, Alexander; Pullen, Frank
Abstract : Rationale: Intramolecular proton migration has been reported to be required for fragmentation by collision‐induced dissociation (CID). If the collision energy is required to provide energy for proton movement to a 'dissociative' site, it may be possible to predict the optimal collision energy for fragmentation using quantum computational chemistry software. A greater understanding of the mechanism(s) of proton migration is necessary. Methods: The product ion spectra of seven compounds were obtained at collision energies stepped in the range from 5 to 50 eV, with precursor ions being generated in positive ion mode by both atmospheric pressure chemical ionisation (APCI) and electrospray ionisation (ESI) (using an ESCi ionisation source with or without corona discharge, respectively). The products ions observed at each collision energy were assessed in terms of structure to ascertain if they were formed as a result of protonation at the initial ionisation site or if the proton had migrated to a dissociative site. Results: Proton migration was shown to be independent of collision energy, stability of the protonated molecule and the distance that the proton moved. Therefore, proton migration is not a barrier to fragmentation as the proton appears to be fully mobile at 5 eV. As proton migration is independent of collision energy for these compounds, whereas fragmentation is energy dependent, protonation at the dissociative site alone is not sufficient to cause bond cleavage. Conclusions: The role of collision energy in bond cleavage may be to increase the vibrational energy of the bond and/or increase the rate of bond cleavage such that it occurs within the residence time of the ion within the collision cell rather than to supply the energy for proton migration. Therefore, quantum chemistry alone cannot predict the collision energies appropriate for fragmentation on the basis of modelling proton movements. Copyright © 2016 John Wiley & Sons, Ltd.